Археозоологічні комплекси зі скіфських курганів - Сєкерська, О.П. (Археологія і давня історія України, 2019)
Публікуються археозоологічні матеріали з чотирьох скіфських курганів ІV ст. до н. е. (Бердянський курган, Бабина Могила, Водяна Могила та курган 1 курганної групи І біля м. Кам’янки-Дніпровської), які зберігаються в Одеському археологічному музеї НАН України. Наводяться дані про видовий склад, вік та стать тварин, використаних у поховально-поминальній обрядовості скіфів. Охарактеризовані морфологічні особливості коней, встановлені особливості їх господарського використання. Archaeozoological studies of the complexes of the Scythian burial mounds Babina and Vodyana Mohyly, the Berdyansk Kurhan and barrow group 1 near the town of Kamenka-Dneprovska allow to make the following generalizations. As the studied materials show, the horse was widely used in the funeral rites of the Scythians. Parts of the carcasses of horses were placed in the burial as a farewell food, meat horses were used for conducting funeral rites, horses were buried with their owners. Sheep and cattle were also used as food. During the funeral rites parts of the carcasses of wild animals — European deer and wild boar — were used as well.